2016
DOI: 10.1159/000438655
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Myrtol Standardized Against Radiation-Induced Lung Injury

Abstract: Background/Aims: As a major complication after thoracic radiotherapy, radiation-induced lung injury (RILI) has great impact on long term quality of life and could result in fatal respiratory insufficiency The present study was aimed to evaluate the effects of Myrtol standardized on RILI, and to investigate the underlying mechanism. Methods: A mouse model of radiation-induced lung injury was generated by using thoracic irradiation with a single dose of 16Gy. Mice were orally administrated with Myrtol (25 mg/kg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Lungs of mice received irradiation at a total dose of 20 Gy and a dose rate of 1 Gy/min. The irradiation source was 60 Co from the radiation center (Faculty of Naval Medicine, Second Military Medical University, China) [21, 22]. …”
Section: Methodsmentioning
confidence: 99%
“…Lungs of mice received irradiation at a total dose of 20 Gy and a dose rate of 1 Gy/min. The irradiation source was 60 Co from the radiation center (Faculty of Naval Medicine, Second Military Medical University, China) [21, 22]. …”
Section: Methodsmentioning
confidence: 99%
“…In the present study, myrtol treatment significantly inhibited the activation of TGF-β1 level in PTKO mice. Zhao et al (13) also observed that myrtol standardized inhibited TGF-β1 expression, and suppressed the levels of TNF-α, IL-1β and IL-6 in radiation-induced lung injury.…”
Section: Discussionmentioning
confidence: 95%
“…Domestic clinical studies have shown that its clinical efficacy is similar to the total curative effect of the import gel myrtol forte group (12). Furthermore, pharmacological and pharmacodynamics studies have demonstrated that myrtol standardized has expectorant anti-inflammatory effects, relieving cough and asthma, and reported reduced toxicity and side-effects (13).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the results from previous studies have shown that inhibiting TNF-α and IL-6 could reduce radiation-induced lung fibrosis (33,34). In addition, research from Zhao and colleagues showed that standardized Myrtol could attenuate RILI by inhibiting TNF-α, IL-1β and IL-6 expression (35). Thus, inhibition of these proinflammatory cytokines may protect against the development of RILI in mice.…”
Section: Discussionmentioning
confidence: 97%